Engineering the Interlayer Spacing by Pre‐Intercalation for High Performance Supercapacitor MXene Electrodes in Room Temperature Ionic Liquid. (18th June 2021) - Liang, Kun; Matsumoto, Ray A.; Zhao, Wei; Osti, Naresh C.; Popov, Ivan; Thapaliya, Bishnu P.; Fleischmann, Simon; Misra, Sudhajit; Prenger, Kaitlyn; Tyagi, Madhusudan; Mamontov, Eugene; Augustyn, Veronica; et al.
Abstract: MXenes exhibit excellent capacitance at high scan rates in sulfuric acid aqueous electrolytes, but the narrow potential window of aqueous electrolytes limits the energy density. Organic electrolytes and room‐temperature ionic liquids (RTILs) can provide higher potential windows, leading to higher energy density. The large cation size of RTIL hinders its intercalation in‐between the layers of MXene limiting the specific capacitance in comparison to aqueous electrolytes. In this work, different chain lengths alkylammonium (AA) cations are intercalated into Ti3 C2 T x, producing variation of MXene interlayer spacings ( d ‐spacing). AA‐cation‐intercalated Ti3 C2 T x (AA‐Ti3 C2 ), exhibits higher specific capacitances, and cycling stabilities than pristine Ti3 C2 T x in 1 m 1‐ethly‐3‐methylimidazolium bis‐(trifluoromethylsulfonyl)‐imide (EMIMTFSI) in acetonitrile and neat EMIMTFSI RTIL electrolytes. Pre‐intercalated MXene with an interlayer spacing of ≈2.2 nm, can deliver a large specific capacitance of 257 F g −1 (1428 mF cm −2 and 492 F cm −3 ) in neat EMIMTFSI electrolyte leading to high energy density. Quasi elastic neutron scattering and electrochemical impedance spectroscopy are used to study the dynamics of confined RTIL in pre‐intercalated MXene. Molecular dynamics simulations suggest significant differences in the structures of RTIL ions and AA cations inside the Ti3 C2 T x interlayer, providing insights into the differences in the observed electrochemical behavior. Abstract : Engineering the interlayer spacing of MXene is achieved by intercalating alkylammonium cations with different chain lengths. An optimum d ‐spacing of 2.2 nm unlocks the interlayer spacing of MXene allowing room‐temperature ionic liquid cations to intercalate in‐between MXene layers for the first time, achieving a capacitance of 257 F g −1 over a large voltage window of 3.2 V.